Data linkage for injury surveillance and research in Australia: perils, pitfalls and potential. (June 2014) - Mitchell, Rebecca J.; Cameron, Cate M.; Bambach, Mike R.
Abstract Objective: To outline some of the key issues for injury‐related data linkage studies in Australia and describe potential applications of data linkage for injury surveillance and research. Methods: Narrative review of data linkage capacity and injury‐related data collection quality in Australia. Results: The establishment of national and state‐based data linkage centres in Australia has been a great leap forward for data linkage capacity for injury research. However, there are still limitations of using data linkage for injury surveillance and research. These are highlighted in the form of key perils and pitfalls, with examples provided. There is still much to be gained for injury research by using data linkage techniques to enhance the information available across the injury continuum, but data quality issues should always be acknowledged. Conclusions: Obtaining authorisation to link injury data collections for national research remains cumbersome. Streamlining of the application process is needed to ensure that injury research is able to be conducted in a timely fashion. Data quality and data linkage rates need to be considered when interpreting research findings. Implications: Streamlining of the application process for research that involves linking data collections would help ensure that research is conducted in a timely fashion.